1992
DOI: 10.1111/j.1432-1033.1992.tb17032.x
|View full text |Cite
|
Sign up to set email alerts
|

Futile cycling of glycogen in Fibrobacter succinogenes as shown by in situ1H‐NMR and 13C‐NMR investigation

Abstract: Glycogen was synthesized during all the growth phases in the rumen anaerobic cellulolytic bacterium Fibrobacter succinogenes. Glycogen synthesis and degradation were monitored using in situ 13C and 'H-NMR spectroscopy in resting cells of F. succinogenes. The cells were incubated at 37°C under anaerobic conditions with [l-13C]glucose and [2-'3C]glucose. 'H-NMR spectra were used to quantify enrichment by ' 3C of metabolism products. Glucose was utilized for energy requirements of the bacterium, essentially via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 31 publications
8
67
0
Order By: Relevance
“…Previous investigations with C. cellulolyticum suggested that the glycogen turnover was involved in carbon flow regulation (5,10). Such observations could be compared with those on F. succinogenes, where glycogen turnover was observed with both cellobiose and cellulose (2,8) and where study of the interaction of carbon and nitrogen metabolisms indicated that addition of ammonium to resting cells of F. succinogenes decreased the flux through glycogen biosynthesis (17).…”
Section: Discussionmentioning
confidence: 95%
“…Previous investigations with C. cellulolyticum suggested that the glycogen turnover was involved in carbon flow regulation (5,10). Such observations could be compared with those on F. succinogenes, where glycogen turnover was observed with both cellobiose and cellulose (2,8) and where study of the interaction of carbon and nitrogen metabolisms indicated that addition of ammonium to resting cells of F. succinogenes decreased the flux through glycogen biosynthesis (17).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Gaudet et al (22) reported that synthesis and turnover of glycogen occurred simultaneously in F. succinogenes S85 when cells were grown with glucose as the carbon source, implying a continuous involvement of glycogen in the carbon metabolism. In other bacteria, such as Methylococcus NCIB 11083, stored glycogen has been reported to serve as a carbon and energy source to maintain viability during carbon starvation (42,53).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in some bacteria, glycogen, like PHB (15), is continuously being turned over (10), and this may explain how the carbon of PHB can be easily shuffled to the synthesis of another polymer such as glycogen. Therefore, the synthesis and degradation of the so-called reserve polymers have to be integrated into the basic cell metabolism.…”
Section: Discussionmentioning
confidence: 99%